Inhibitory effect of Patrinia scabiosifolia Link on the development of atopic dermatitis-like lesions in human keratinocytes and NC/Nga mice. (12th July 2017) - Cha, Kyung-Jae; Im, Mi Ae; Gu, Ayoung; Kim, Da Hye; Lee, Daye; Lee, Jeong Soo; Lee, Ji-Sook; Kim, In Sik
Abstract: Ethnopharmacological relevance: Atopic dermatitis (AD) is a chronic pruritic and inflammatory disease occurring in skin. Patrinia scabiosifolia Link (PS), a member of the Patrinia genus ( Caprifoliaceae family), has traditionally been used in folk medicines to treat various inflammatory diseases such as acute appendicitis, ulcerative colitis, and pelvic inflammation in Korea and other parts of East Asia. Aim of the study: This study investigated the anti-inflammatory effects of PS on AD in vitro and in vivo . Materials and methods: Whole PS plants were dried, powdered, and then underwent extraction with DMSO. Both ELISA and western blotting were performed to evaluate cytokine concentration and the expression and activation of filaggrin and signaling proteins. Five-week‐old female NC/Nga mice were used as an AD-like mouse model by treating them with 2, 4-dinitrochlorobenzene (DNCB). Results: In human keratinocytic HaCaT cells, PS extract inhibited the production of IL‐8, and TARC, which had been increased by TNF-α and IFN-γ. The TNF-α and IFN-γ suppressed filaggrin expression was associated with phosphorylation of JNK1 and JNK2, and NF-κB translocation. PS recovered the inhibition of filaggrin expression induced by TNF-α and IFN-γ by blocking the activation of JNK1/2, and NF-κB by the IFN-γ and TNF-α treatment. The in vivo experiment results showed that, compared to DNCB treatment PS administration reduced thickening of the epidermis and infiltration of inflammatory cells into the dermis. Moreover, the decrease of filaggrin expression due to DNCB treatment was recovered by PS administration. The serum IgE level was decreased by PS treatment. Additionally, secretions of IL-4, IL-5, IL-13, and eotaxin in splenocytes were lower in the PS-treated group than in the DNCB group. Conclusion: PS may attenuate the development of AD‐like lesions by increasing filaggrin expression and lowering IgE and inflammatory cytokine levels. These results indicate the potential for development of a PS-based drug treatment for AD. Graphical abstract: Anti-allergic effect of PS on allergic dermatitis-like NC/Nga mice: Possible mechanisms